Blood brother : Jonathan Daniels and his sacrifice for civil rights - Wallace, Rich; Wallace, Sandra Neil (2016)
"Jonathan Daniels, a white seminary student from New Hampshire, traveled to Selma, Alabama, in 1965 to help with voter registration of black residents. After the voting rights marches, he remained in Alabama, in the area known as (3z(BBloody Lowndes,(3y (Ban extremely dangerous area for white freedom fighters, to assist civil rights workers. Five months later, Jonathan Daniels was shot and killed while saving the life of Ruby Sales, a black teenager. Through Danielss poignant letters, papers, photographs, and taped interviews, authors Rich Wallace and Sandra Neil Wallace explore what led Daniels to the moment of his death, the trial of his murderer, and how these events helped reshape both the legal and political climate of Lowndes County and the nation."--Publisher's website.s
Crossing boundaries -- Behind the eight ball -- Military interference -- Quietly frantic -- Bloody Sunday -- Open hostility -- Higher stakes -- A life in danger -- Segregated worship -- Bloody Lowndes -- Stripped of color -- No back doors -- Jailed -- An eerie quiet -- Saying goodbye -- The Coleman trial -- The southern way -- Jonathan's revolution -- Epilogue: a life continues -- A note from the authors -- The ears have it: a note on our research -- Timeline -- Bibliography -- For further information -- Source notes -- Index.
Includes bibliographical references (pages 329-337) and index.
Keywords: Daniels, Jonathan Myrick, -- 1939-1965.; Civil rights workers -- United States -- Biography; African Americans -- Civil rights; Murder -- Alabama -- Hayneville -- History -- 20th century; Civil rights movements -- United States -- History -- 20th century; Social justice -- United States; Alabama -- Race relations